A SATISFACTION OF OUTPATIENTS TOWARDS HEALTH SERVICE QUALITY AT BANJARMASIN SIAGA SPECIAL SURGICAL HOSPITAL: A SATISFACTION OF OUTPATIENTS TOWARDS HEALTH SERVICE QUALITY AT BANJARMASIN SIAGA SPECIAL SURGICAL HOSPITAL - Diaty, Rima; Purwanti, Sri (JURNAL TERAS KESEHATAN, 2024)
There is a relationship between responsiveness and tangible factors with outpatient satisfaction at Banjarmasin Siaga Special Surgical Hospital. However, there is no relationship between reliability, assurance, and empathy with outpatient satisfaction at Banjarmasin Siaga Special Surgical Hospital. Keywords: Patient satisfaction, outpatient care, service quality, hospital